2009
DOI: 10.1007/s00540-009-0744-5
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cognitive decline

Abstract: Memory loss and lack of concentration are symptoms that frequently occur in patients who have undergone a surgical procedure. Although cognitive function can be assessed using neuropsychological tests, reliable diagnosis of postoperative cognitive decline (POCD) appears to be difficult. Therefore, the true incidence of POCD is unknown. Severe POCD, which is apparent even without neuropsychological testing, is reported most frequently after cardiac and hip-replacement surgery. In these cases, POCD probably refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 39 publications
(46 reference statements)
0
61
1
1
Order By: Relevance
“…Such insights may allow the development of strategies to prevent and treat memory disorders associated with anesthetic states, such as intraoperative awareness [149][150][151] and memory deficits in the postoperative period. [152][153][154] …”
Section: Discussionmentioning
confidence: 99%
“…Such insights may allow the development of strategies to prevent and treat memory disorders associated with anesthetic states, such as intraoperative awareness [149][150][151] and memory deficits in the postoperative period. [152][153][154] …”
Section: Discussionmentioning
confidence: 99%
“…However, some authors even stated that POCD rarely occurs, but is only based on wrongful interpretations of the results of neuropsychological tests (11). An alarming prevalence of POCD, of more than 30% at 1 year after coronary bypass surgery, decreases to 10% when applying a more conservative definition (12). Therefore, it is possible that the arbi-…”
Section: Definition and Prevalence Of Pocdmentioning
confidence: 99%
“…However, several months after surgery, the incidence decreases to less than half of the patients, and at one year after surgery, decreases to approximately one-quarter of patients. Although it may be true that most of the early cognitive loss is transient, multiple longitudinal studies demonstrated that, in some cases, it persists for several years after surgery [10,11].…”
Section: Current Understanding Of Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…Many previous studies demonstrated that this complication is associated with the duration of cardiopulmonary bypass, valve surgery and impaired cardiac function. Embolization of particulate and gaseous material into the cerebral microvasculature, resulting in focal areas of cerebral ischemia, has been best studied as the mechanism underlying cognitive dysfunction following cardiac and orthopedic surgeries [11,12]. However, it is still controversial whether cerebral embolization is the cause of such cardiac surgery-related cognitive impairment, since, in some studies, the rates of cognitive dysfunction were similar even after coronary artery bypass surgery without cardiopulmonary bypass [13].…”
Section: Risk Factors and Proposed Mechanisms Of Cognitive Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation